High-voltage current sensing with nitrogen-vacancy centers in diamond - Shao-Chun Zhang; Long Zhao; Ru-Jia Qiu; Jia-Qi Geng; Teng Tian; Bo-Wen Zhao; Yong Liu; Long-Kun Shan; Xiang-Dong Chen; Guang-Can Guo; Fang-Wen Sun (APL Photonics)
The negatively charged nitrogen-vacancy color center in diamond exhibits several remarkable properties, which make it widely used in magnetic field sensing. In particular, the magnetic field measurements can be traced back to frequency, which makes diamond sensors promising for high-precision current measurement. Here, we develop a quantum current transformer (QCT) with four fiberized diamond sensors uniformly toroidally distributed in a magnetic shielding loop. We proposed fluorescence signal treatments of frequency-doubled conversion and weighted averaging under a zero bias magnetic field, which can reconstruct the 50 Hz alternating-current waveform. A maximum accuracy of 0.05% for AC amplitude measurements is achieved over a highly linear range of 0–1000 A. In addition, tracing two resonance frequencies simultaneously enabled the suppression of temperature drift in the current measurement. Finally, we apply this QCT to current monitoring in a 110 kV substation, verifying its practicality in the power supply network. Such a QCT can provide a robust and scalable platform for current quantum sensing technologies for high-voltage power transmission while reducing the complexity of operation and maintenance.